Mitochondrial complex I deficiency leads to increased production of superoxide radicals and induction of superoxide dismutase. - Pitkanen, S (1996)
Mitochondria were isolated from skin fibroblast cultures derived from healthy individuals (controls) and from a group patients with complex I (NADH-CoQ reductase) deficiency of the mitochondrial respiratory chain. The complex I deficient patients included those with fatal infantile lactic acidosis (FILA), cardiomyopathy with cataracts (CC), hepatopathy with tubulopathy (HT), Leigh's disease (LD), cataracts and developmental delay (CD), and lactic acidemia in the neonatal period followed by mild symptoms (MS). Production of superoxide radicals, on addition of NADH, were measured using the luminometric probe lucigenin with isolated fibroblast mitochondrial membranes. Superoxide production rates were highest with CD and decreased in the order CD >> MS > LD > control > HT > FILA = CC. The quantity of Mn-superoxide dismutase (MnSOD), as measured by ELISA techniques, however, was highest in CC and FILA and lowest in CD. Plots of MnSOD quantity versus superoxide production showed an inverse relationship for most conditions with complex I deficiency. We hypothesize that oxygen radical production is increased when complex I activity is compromised. However, the observed superoxide production rates are modulated by the variant induction of MnSOD which decreases the rates, sometimes below those seen in control fibroblast mitochondria. In turn, we show that the variant induction of MnSOD is most likely a function of the change in the redox state of the cell experienced rather than a result of the complex I defect per se.